The role of visual appeal in Malaysian fast-food social media advertising - Sulaiman, Shahrunizam; Mohamad Fairuz, Nur Syafiqah; Mohd Tahir, Hanafi (Journal of Islamic, Social, Economics and Development, 2025)
The rapid evolution of technology has significantly shaped the Malaysian food and beverage (F&B) industry, particularly in marketing and consumer engagement. Undeniably, social media being a popular platform these days effectively reaches the target market. Social media platforms, powered by advanced technology, serve as critical tools for publishing information and promoting brands. This technological shift has made advertisements more general and significant, especially for fast food brands. Young individuals are highly susceptible to these marketing campaigns due to their heavy reliance on social media platforms. Fast food brands in Malaysia are leveraging vibrant graphic elements, catchy slogans, and appealing imagery in their advertisements to capture attention and purchasing decisions in a crowded digital space. These elements, designed to resonate with consumers, increase engagement and drive conversion rates. The competitive nature of the digital advertising view has compelled marketers to continuously innovate and adapt strategies that align with consumer preferences and behaviour, ensuring sustained relevance and appeal. To conclude, visual appeal is an essential part of effective fast-food promotion, especially on social media, which is always changing. Social media platforms like Instagram, TikTok, and Facebook are becoming important places for people to interact with each other.